A Histological and Physiological Analysis to Assess The Protective Function Rats’ Hepatotoxicity Caused by Acetaminophen is Inhibited by an Alcoholic Extract of Garden Cress Seeds (Lepidium Sativum) - Saleh, Abeer Majeed; Salim, Dina Kamal (American Journal of Botany and Bioengineering, 2026)
To assess how well the alcoholic extract of Garden Cress (Lepidium sativum) protects against acetaminophen-induced hepatotoxicity by enhancing erythropoietin levels and other physiological indicators. Protein, dietary fiber, vitamins, minerals, and vital amino acids are all abundant in garden cress seeds. Additionally, they contain phytochemicals that have been shown to help decrease blood triglycerides and cholesterol as well as prevent and inhibit the formation of cancer. One of the most popular and extensively used analgesics and antipyretics in the world is acetaminophen. It is an appropriate drug for cress seed extract, which is crucial for shielding the liver from carbon tetrachloride (CCl-4) damage. A study using rats showed that adding 200–400 mg/kg of cress seed extract to their daily diet significantly reduced hepatotoxicity. The rats were split into three groups: a control group, a group that was treated to uronic acid, and a group that was subjected to Ccl-4 to cause liver injury. Despite this, the number of documented cases of liver damage brought on by excessive dosages of the medication has been steadily rising annually throughout the world.